The Implementation of Character Education in EFL Class - Sandra Hidayat; Feny Martina; Ali Akbarjono (Yayasan Karinosseff Muda Indonesia, 2021)
This study aims to explore the implementation of character education values based on the five main values of strengthening character education. The method employed in this study was descriptive qualitative. The sample consisted of two English teachers in SMAN 4 Mukomuko. The researcher used 5 main values of character education as the research limitation in conducting this study. The technique of data collection were observation, interview, and documentation. The result of this study shows that teachers in SMAN 4 Mukomuko have implemented the 5 main values in strengthening character education, such as religion, nationalism, integrity, independence, and mutual cooperation value. The teachers show and teach the value of character education in the school well. They have been carried out quite well in the teaching and learning process. Although there were obstacles faced by teachers at SMAN 4 Mukomuko, the school were also constantly looking for solution to overcome the problems by strengthening teachers cooperation and building good relationship between parents of student and SMAN 4 Mukomuko.